2000
DOI: 10.1017/s0022149x00000056
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal helminths of spiny mice (Acomys cahirinus dimidiatus) from St Katherine's Protectorate in the Sinai, Egypt

Abstract: Spiny mice,Acomys cahirinus dimidiatus, inhabiting the wadis close to St Katherine in the mountains of the Sinai peninsula, were trapped and their helminth parasites were studied. Sixty one mice provided faeces for analysis and 27 were killed and autopsied. Six species of helminths were recorded (the spirurid nematodes,Protospirura muricola(74.1%) andMastophorus muris(11.1%), the oxyuroid nematodes,Dentostomella kuntzi(59.3%),Aspiculuris africana(3.7%), andSyphacia minuta(3.7%) and the hymenolepidid cestodeRod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 29 publications
5
44
0
Order By: Relevance
“…However, differences were noted between the wild worm populations and those cultured in laboratory mice. In particular, the positions of the deirids and nerve-ring of cultured worms were significantly further from the anterior end than those from wild worms, even after taking Gedoelst, 1916;Ortlepp, 1924;Baylis, 1928;Joyeux et al, 1928;Brumpt, 1931;Tubangi, 1931;Foster & Johnson, 1939;Dollfus & Chabaud, 1955;Morel, 1959;Myers & Kuntz, 1960;Quentin, 1969;Campos & Vargas, 1978;Ashour, 1980;Scharff et al, 1993Scharff et al, , 1997Behnke et al, 2000;Asakawa & Nicolas, 2003;Tenora et al, 2003;Petrzelkova et al, 2006;Waugh et al, 2006; this study worm lengths into consideration (in both cases there was no effect of sex nor any interactions involving sex in full factorial models with length as a covariate, so models were re-run with just site as the factor and worm length as a covariate; the main effects of site for deirids F 3,55 = 31.1, P \ 0.001, model R 2 = 64.9%, and for nerve-ring F 3,58 = 11.2, P \ 0.001, model R 2 = 46.9%). The position of the excretory pore was also further from the anterior end in passaged worms (F 3,50 = 12.9, P \ 0.001, model R 2 = 48.5%).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, differences were noted between the wild worm populations and those cultured in laboratory mice. In particular, the positions of the deirids and nerve-ring of cultured worms were significantly further from the anterior end than those from wild worms, even after taking Gedoelst, 1916;Ortlepp, 1924;Baylis, 1928;Joyeux et al, 1928;Brumpt, 1931;Tubangi, 1931;Foster & Johnson, 1939;Dollfus & Chabaud, 1955;Morel, 1959;Myers & Kuntz, 1960;Quentin, 1969;Campos & Vargas, 1978;Ashour, 1980;Scharff et al, 1993Scharff et al, , 1997Behnke et al, 2000;Asakawa & Nicolas, 2003;Tenora et al, 2003;Petrzelkova et al, 2006;Waugh et al, 2006; this study worm lengths into consideration (in both cases there was no effect of sex nor any interactions involving sex in full factorial models with length as a covariate, so models were re-run with just site as the factor and worm length as a covariate; the main effects of site for deirids F 3,55 = 31.1, P \ 0.001, model R 2 = 64.9%, and for nerve-ring F 3,58 = 11.2, P \ 0.001, model R 2 = 46.9%). The position of the excretory pore was also further from the anterior end in passaged worms (F 3,50 = 12.9, P \ 0.001, model R 2 = 48.5%).…”
Section: Resultsmentioning
confidence: 98%
“…Hosts were collected (see Behnke et al, 2000Behnke et al, , 2004Bajer et al, 2006) during June, 1997, August and September, 2000, and August and September, 2004 from a variety of locations around the University of Suez Canal Environmental Research Centre (ERC) in the town of St Katherine. The local environment and general characteristics of these locations have been described in Behnke et al (2000Behnke et al ( , 2004. A. dimidiatus were caught alive using Sherman traps and up to 40% of captured animals from each site were then culled (by prior agreement with Park Authorities) for the examination of endoparasites.…”
Section: Methodsmentioning
confidence: 99%
“…In our earlier papers (Behnke et al , 2000, 2004; Barnard et al , 2003 b ), we referred to the host spiny mouse as Acomys cahirinus dimidiatus . Here we refer to the host as Ac.…”
Section: Methodsmentioning
confidence: 99%
“…In earlier papers we showed that the helminth communities of bank voles vary markedly between subpopulations of voles living in forest patches that are ecologically very similar but segregated from each other by natural barriers (Behnke et al , 2001; Barnard et al , 2002, 2003 a ), and that the key indicators of helminth community structure are stable in the medium term (Bajer et al , 2005). Similarly, helminth communities in spiny mice Acomys dimidiatus differ profoundly between neighbouring but isolated wadis in the mountains of the Sinai Peninsula (Behnke et al , 2000, 2004; Barnard et al , 2003 b ). In contrast to studies of rodent helminths, there are few studies of site‐specific variation in haemoparasitic infections or in protozoan infections of the intestinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…have been examined for endoparasites by several authors, who reported mostly cestodes and oxyurid nematodes (Hussein and Kalantan 1993;Behnke et al 2000;Barnard et al 2003). Only a single Eimeria species, E. cahirinensis Couch, Blaustein, Duszynski, Shenbrot andNevo, 1997 (Couch et al 1997), identified on the basis of oocyst morphology, has been reported from these hosts.…”
Section: Discussionmentioning
confidence: 99%